Delimitation of the ‘Public’ and Freedom of Conscience: Catholics’ Survival Tactics in Legal Discourses in Utrecht, 1630-1659 - Yasuhira, Genji (Early Modern Low Countries, 2019)
This article aims to clarify Catholics’ survival tactics in discourses by analysing legal proceedings against them in the city of Utrecht from 1630 until 1659. This period saw a tendency towards Reformed confessionalisation, as is apparent from the rise in the number of such trials. However, despite the advent of anti-Catholic legislation under increasing pressure from the Reformed Church, Reformed confessionalisation was not completed, as the Catholic presence in the public sphere of Utrecht was never extinguished. Backed by their civic status, and with the aid of defenders in (supra-confessional) socio-judicial networks, accused Catholics developed a variety of discourses during legal proceedings. Obedient conformity to the existing norm of the public/private distinction was just one of the various discursive tactics for survival employed by Catholics in Utrecht. Despite the crucial discontinuity caused by the Protestant Reformation and the Dutch Revolt, Catholics continued to be actors in the constant and communal process of delimitation of the ‘public’. Members of the Catholic social elite in particular could actively create space for survival by discursively mobilising alternative interpretations of the ‘public’ and ‘conscience’ that retained medieval legacies, without conceptualising ‘privacy’ in the modern sense.